Exploring the worldwide patent surge. Issue 2 (17th February 2016) - Fink, Carsten; Khan, Mosahid; Zhou, Hao
Abstract : Worldwide patent filings are at historically unprecedented levels. In 2011, the total number of patent applications for the first time exceeded two million – double the approximately 1.05 million patents filed in 1995. Understanding what is behind this growth is important, as it may indicate faster technological progress, new innovation models and strategic shifts in how companies use the patent system. Policy-makers need to understand what drives the growth in patenting worldwide, not least to evaluate how the patent system can cope with the increasing flow of applications. A number of studies have looked at the growth in patent filings in individual countries, but have not focused on the world as a whole. This paper seeks to fill this gap by providing an analysis of global patenting trends using the most comprehensive data currently available. Among other things, it finds that subsequent patent filings – additional filings of the same invention, mostly in additional countries – contributed considerably to the growth in filings worldwide, pointing to globalization as one important driver of filing growth. However, no single factor can fully explain the marked increase in the use of the patent system.